Shape transitions in proton-rich Ho and Tm isotopes - Zhu Jian-Yu; Chong, Qi; Liu Meng-Xi; Cui Xiao; Xu Fu-Rong (CHINESE PHYSICS C, 2009)
Total Routhian Surface (TRS) calculations have been performed for even-even nuclei along proton drip line to study nuclear ground-state deformations; as well as the odd proton nuclei Ho and Tm isotopes. The drip line nuclei show the expected shape transition with the shell effects. Ground-state shape changes from prolate to oblate at (143)Ho and (145)Tm in these two isotopes, which is due to the gamma instability around N = 76.